The Influence of Influencer Marketing, Video Content, and Social Media Interaction on Generation Z's Buying Interest in Online Fashion Products - Annis Yuniar Sabilla; Fatih Fuadi; Liya Ermawati (Majapahit Journal of Islamic Finance and Management, 2025)
This study used a quantitative approach to determine the influence of influencer marketing, video content, and social media interactions on Generation Z's purchasing interests. Data collected through questionnaires were used as a source of research. The study involved Generation Z. Probability sampling was used for sampling, the sample size was calculated by lemeshow formula for 100 respondents, and PLS (Partical Least Square) was used to analyze the data. PLS is a structural equation modeling (SEM) model that uses an approach based on variance or component based structural equation modeling. SmartPls 4 produces data processing results. This study shows that marketing influence factors have a positive but not significant effect on Gen Z's interest in buying fashion items online. There is a positive and significant influence of video content and social media interaction variables on Gen Z's interest in buying fashion products via the internet.